Diffusion‐weighted magnetic resonance imaging of the fetal brain in intrauterine growth restriction. (6th July 2017) - Arthurs, O. J.; Rega, A.; Guimiot, F.; Belarbi, N.; Rosenblatt, J.; Biran, V.; Elmaleh, M.; Sebag, G.; Alison, M.
ABSTRACT: Objective: Diffusion‐weighted magnetic resonance imaging (DWI) is a sensitive method for assessing brain maturation and detecting brain lesions, providing apparent diffusion coefficient (ADC) values as a measure of water diffusion. Abnormal ADC values are seen in ischemic brain lesions, such as those associated with acute or chronic hypoxia. The aim of this study was to assess whether ADC values in the fetal brain were different in fetuses with severe intrauterine growth restriction (IUGR) compared with normal controls. Methods: Brain magnetic resonance imaging (MRI) with single‐shot axial DWI (b = 0 and b = 700 s/mm 2 ) was performed in 30 fetuses with severe IUGR (estimated fetal weight < 3 rd centile with absent or reversed umbilical artery Doppler flow) and in 24 normal controls of similar gestational age. Brain morphology and biometry were analyzed. ADC values were measured in frontal and occipital white matter, centrum semiovale, thalami, cerebellar hemisphere and pons. Frontal–occipital and frontal–cerebellar ADC ratios were calculated, and values were compared between IUGR fetuses and controls. Results: There was no difference in gestational age at MRI between IUGR and control fetuses (IUGR, 30.2 ± 1.6 weeks vs controls, 30.7 ± 1.4 weeks). Fetal brain morphology and signals were normal in all fetuses. Brain dimensions (supratentorial ± infratentorial) were decreased ( Z ‐score, < –2) in 20 (66.7%) IUGR fetuses. Compared with controls, IUGR fetuses had significantly lower ADC values in frontal white matter (1.97 ± 0.23 vs 2.17 ± 0.22 × 10 –3 mm 2 /s; P < 0.0001), thalami (1.04 ± 0.15 vs 1.13 ± 0.10 ×10 –3 mm 2 /s; P = 0.0002), centrum semiovale (1.86 ± 0.22 vs 1.97 ± 0.23 ×10 –3 mm 2 /s; P = 0.01) and pons (0.85 ± 0.19 vs 0.94 ± 0.12 ×10 –3 mm 2 /s; P = 0.043). IUGR fetuses had a lower frontal–occipital ADC ratio than did normal fetuses (1.00 ± 0.11 vs 1.08 ± 0.05; P = 0.003). Conclusions: ADC values in IUGR fetuses were significantly lower than in normal controls in the frontal white matter, thalami, centrum semiovale and pons, suggesting abnormal maturation in these regions. However, the prognostic value of these ADC changes is still unknown. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd. Abstract : Linked Comment: Ultrasound Obstet Gynecol 2017; 50: 18–19